Asymmetric Flexible MXene‐Reduced Graphene Oxide Micro‐Supercapacitor. (27th November 2017) - Couly, Cedric; Alhabeb, Mohamed; Van Aken, Katherine L.; Kurra, Narendra; Gomes, Luisa; Navarro‐Suárez, Adriana M.; Anasori, Babak; Alshareef, Husam N.; Gogotsi, Yury
Abstract: Current microfabrication of micro‐supercapacitors often involves multistep processing and delicate lithography protocols. In this study, simple fabrication of an asymmetric MXene‐based micro‐supercapacitor that is flexible, binder‐free, and current‐collector‐free is reported. The interdigitated device architecture is fabricated using a custom‐made mask and a scalable spray coating technique onto a flexible, transparent substrate. The electrode materials are comprised of titanium carbide MXene (Ti3 C2 T x ) and reduced graphene oxide (rGO), which are both 2D layered materials that contribute to the fast ion diffusion in the interdigitated electrode architecture. This MXene‐based asymmetric micro‐supercapacitor operates at a 1 V voltage window, while retaining 97% of the initial capacitance after ten thousand cycles, and exhibits an energy density of 8.6 mW h cm −3 at a power density of 0.2 W cm −3 . Further, these micro‐supercapacitors show a high level of flexibility during mechanical bending. Utilizing the ability of Ti3 C2 T x ‐MXene electrodes to operate at negative potentials in aqueous electrolytes, it is shown that using Ti3 C2 T x as a negative electrode and rGO as a positive one in asymmetric architectures is a promising strategy for increasing both energy and power densities of micro‐supercapacitors. Abstract : Utilizing the ability of Ti3 C2 T x ‐MXene electrodes to operate at negative potentials in aqueous electrolytes, it is shown that using Ti3 C2 T x as a negative electrode and rGO as a positive one in asymmetric architectures is a promising strategy for increasing both energy and power densities of micro‐supercapacitors.